SYAFA'AT (INTERCESSION) IN AL-QUR'AN PERSPECTIVE (A Study on the Interpretation of Maudhu'i) - Zaenal Arifin (Universitas Islam Negeri Ar-Raniry, 2019)
This study aims to find out the Al-Qur'an's view on the theme of intercession, understand intercession in relation to other than Allah, such as Angels, Rasulallah, Al-Qur'an and know who has the right to obtain intercession and its criteria. The study was designed through descriptive research conducted with a thematic qualitative approach with the maudhu'i method. The subjects in this study are library research, that is, all data sources come from written materials related to the topics discussed. Data analysis in this study uses text analysis. The results of this study indicate that syafa'at is still being discussed by the scholars, but most of the scholars say that the syafa'at exists later on the Day of Judgment. As for the group that believes that there is Shafi'i is the Shiite and Ahlussunah groups, while the Mu'tazilah group believes that there is no Syafa'at in the afterlife, of course with their respective arguments. As for those who can give syafa'at are angels, prophets, pious people and good deeds, of course after getting permission and blessings from God.